Accumulation of Heavy Metals (Cu and Pb) In Two Consumed Fishes from Musi River Estuary, South Sumatera - Wike Ayu Eka Putri; Dietriech G Bengen; Tri Prartono; Etty Riani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Fish is one of the protein sources for humans which its existence is susceptible to the contamination, one of which is the heavy metal. The lack of information regarding the content of heavy metal in the edible fish in South Sumatera makes this study important to be done. This study was aimed to analyze the concentration of heavy metal in two species of edible fishes at Musi River Estuary site. The study was conducted in the estuary section of Musi River from September to November 2014. The heavy metals of Cu and Pb in the water and in the fish organs were analyzed using AAS with a type of SpektrA A-20 Variant Plus using a mixture of Air-Acetylene flame. The result showed the variation of Cu and Pb concentrations in each of species and three organs observed. The concentration of Cu and Pb in the liver was higher than in the gills and the muscle (liver>gills>muscle). The concentration of Cu and Pb in the muscle of all fish species were not exceed the safe limit for consumption. Keywords: Cu and Pb, consumed fish, Musi River estuary